ROLE OF TECHNOLOGY IN ENHANCING THE VISIBILITY AND TRACEABILITY IN THE AGRI-FOOD SUPPLY CHAIN MANAGEMENT - Richa, Saxena; Satyendra, Arya (INTI International University, 2023)
This study examines how technology is critical in improving traceability and visibility in the complex ecology of agri-food supply chain management. The agri-food business recognizes that incorporating advanced technologies is essential in an era distinguished by changing customer preferences, strict regulations, and a rising emphasis on sustainability. This study offers a comprehensive analysis of the ways in which technological advancements help the Agri-food supply chain as whole overcome obstacles, become more efficient, and maintain its integrity. The study investigates the advantages of Radio-Frequency Identification (RFID) technology and Internet of Things (IoT) devices for real-time monitoring of vital parameters like temperature, humidity, and product placement. Implementing blockchain technology is closely examined because of its potential to establish end-to-end traceability, strengthen the integrity of the supply chain, and produce an indestructible and transparent database. The purpose of this research paper is to present an in-depth understanding of the ways in which technology is transforming the agri-food supply chain. The findings show how important these technical developments are to fulfilling customer demands, ensuring food safety, and promoting sustainability in the agri-food sector.